Answer: 2x+3
Step-by-step explanation:
9x+18=6y-3x Our goal is to isolate y.
Let's add 3x to both sides of the equation to cancel out that -3x on the right side.
12x+18=6y Because all of these integers are divisible by the gcf of 6, we can divide both sides of the equation by 6.
2x+3=y
Answer:
x=4.5
Step-by-step explanation:
Using sohcahtoa we know tangent is equal to (length of side opposite to the angle ) / (lenth of side adjacent to the angle)
therefore: tan (theta) = (x-3) / (x) = 1 / 3
now cross multiply
3(x-3) = x
now solve for x
3x - 9 = x
-9= -2x
x= 4.5
Answer:
12(4) +6
48+6 = 54
y=54
Step-by-step explanation:
Answer:
No, h = (-23)/5
Step-by-step explanation:
Solve for h:
3 (4 - 6 h) - 7 h = 127
3 (4 - 6 h) = 12 - 18 h:
12 - 18 h - 7 h = 127
-18 h - 7 h = -25 h:
-25 h + 12 = 127
Subtract 12 from both sides:
(12 - 12) - 25 h = 127 - 12
12 - 12 = 0:
-25 h = 127 - 12
127 - 12 = 115:
-25 h = 115
Divide both sides of -25 h = 115 by -25:
(-25 h)/(-25) = 115/(-25)
(-25)/(-25) = 1:
h = 115/(-25)
The gcd of 115 and -25 is 5, so 115/(-25) = (5×23)/(5 (-5)) = 5/5×23/(-5) = 23/(-5):
h = 23/(-5)
Multiply numerator and denominator of 23/(-5) by -1:
Answer: h = (-23)/5
Answer:
a=sqrt(d)-b, a=-sqrt(d)-b
Step-by-step explanation:
(a+b)^2=d
(a+b)=sqrt(d)
a+b=sqrt(d), a+b=-sqrt(d)
a=sqrt(d)-b, a=-sqrt(d)-b